Relationships between university instructors’ and preservice teachers’ content knowledge - (:unkn) unknown (SAGE Publications Ltd, 2022)
The purpose of this study was to examine the relationships between instructors’ common content knowledge, knowledge of instructional tasks, and knowledge of student errors and preservice teachers’ common content knowledge and knowledge of instructional tasks in gymnastics, soccer, and volleyball. Participants were 23 university instructors and 819 preservice teachers enrolled in 9 physical education teacher education programs in Turkey. Common content knowledge and knowledge of student errors were measured using validated gymnastics, soccer, and volleyball knowledge tests. Knowledge of instructional tasks was measured by content maps and assessed using a specialized content knowledge index for each sport. A Spearman's rank… correlation coefficient was used to measure the degree of relationships. There were significant positive relationships between instructors’ and preservice teachers’ common content knowledge levels of gymnastics (r = 0.82, p < 0.01), soccer (r = 0.94, p < 0.01), and volleyball (r = 0.85, p < 0.01) and instructors’ knowledge of student errors and preservice teachers’ common content knowledge levels of gymnastics (r = 0.87, p < 0.01), soccer (r = 0.94, p < 0.01), and volleyball (r = 0.93, p < 0.01). A significant positive relationship between instructors’ knowledge of student errors and preservice teachers’ gymnastics knowledge of instructional tasks was found (r = 0.77, p < 0.05). There was no statistically significant correlation between instructors’ and preservice teachers’ knowledge of instructional tasks. Physical education teacher education and professional development programs should focus on increasing instructors’ and preservice teachers’ knowledge of student errors and knowledge of instructional tasks. © The Author(s) 2022.
Keywords: common content knowledge; instructional tasks; misconceptions; specialized content knowledge; Student errors